The impact of smoking and alcohol consumption on rosacea: a multivariable Mendelian randomization study - Chu, Zhaowei; Yi, Mengyao; Yan, Cong; Li, Bingjie; Zhang, Huan; Guo, Kun; Geng, Songmei (Frontiers in Public Health, 2024)
Backgrounds Observational studies have shown that cigarette smoking is inversely associated with risk of rosacea, However, it remains uncertain whether this association is causal or it is a result of reverse causation, and whether this association is affected by drinking behaviors. Methods This study utilized the summary-level data from the largest genome-wide association study (GWAS) for smoking, alcohol consumption, and rosacea. The objective was to investigate the effect of genetically predicted exposures to smoking and alcohol consumption on the risk of developing rosacea. Two-sample bidirectional Mendelian randomization (MR) was applied, accompanied by sensitive analyses to validate the robustness of findings. Furthermore, multivariable MR was conducted to evaluate the direct impact of smoking on rosacea. Results A decreased risk of rosacea was observed in individuals with genetically predicted lifetime smoking [odds ratio (OR)MR − IVW = 0.53; 95% confidence interval (CI), 0.318–0.897; P = 0.017], and number of cigarettes per day (ORMR − IVW = 0.55; 95% CI, 0.358–0.845; P = 0.006). However, no significant associations were found between initiation of regular smoking, smoking cessation, smoking initiation, alcohol consumption and rosacea. Reverse MR analysis did not show any associations between genetic liability toward rosacea and smoking or alcohol drinking. Importantly, the effect of lifetime smoking and the number of cigarettes per day on rosacea remained significant even after adjusting for alcohol consumption in multivariable MR analysis. Conclusion Smoking was causally related to a lower risk of rosacea, while alcohol consumption does not appear to be associated with risk of rosacea.